2014
DOI: 10.1055/s-0034-1395530
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between the Brain Natriuretic Peptide (BNP) Level and Remission of Diabetic Nephropathy with Microalbuminuria: A 3-Year Follow-Up Study

Abstract: The aim of the study was to examine the relationship between the brain natriuretic peptide (BNP) level and progression or remission of diabetic nephropathy with microalbuminuria for 3 years. The subjects were 100 Japanese type 2 diabetes mellitus outpatients with microalbuminuria. Associations between metabolic parameters at baseline [HbA1c, systolic blood pressure (SBP), urine albumin-creatinine ratio (ACR), estimated glomerular filtration rate (eGFR), and BNP] and the progression or remission of diabetic nep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Persistent hyperglycemia can induce glomerular mesangial hyperplasia, resulting in basement membrane thickening and glomerular capillary wall sclerosis, ultimately leading to the occurrence of proteinuria. On the other hand, persistent hyperglycemia causes the glomerulus to be in a state of hyperperfusion and hyperfiltration, resulting in capillary sclerosis and changes in vascular permeability, which ultimately leads to plasma protein deposition on capillary walls, progressive vascular hyperplasia, hyaline degeneration and intravascular thrombosis [ 66 ]. Second, blood glucose fluctuates greatly.…”
Section: Discussionmentioning
confidence: 99%
“…Persistent hyperglycemia can induce glomerular mesangial hyperplasia, resulting in basement membrane thickening and glomerular capillary wall sclerosis, ultimately leading to the occurrence of proteinuria. On the other hand, persistent hyperglycemia causes the glomerulus to be in a state of hyperperfusion and hyperfiltration, resulting in capillary sclerosis and changes in vascular permeability, which ultimately leads to plasma protein deposition on capillary walls, progressive vascular hyperplasia, hyaline degeneration and intravascular thrombosis [ 66 ]. Second, blood glucose fluctuates greatly.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of BNP as a predictive factor in diabetic nephropathy has not been established. We previously reported that in diabetes with microalbuminuria the baseline BNP level is independently associated with the annual decline in estimated glomerular filtration rate (eGFR) [19] and prognosis of diabetic nephropathy for 3 years [20]. In the current study, we examined the relationship between the BNP level and prognosis of diabetic nephropathy (progression of diabetic nephropathy, cardiovascular events, and death) over a follow-up period of 7 years.…”
Section: Introductionmentioning
confidence: 94%
“…Experimental studies have shown that BNP is cleaved by DPP-4 to BNP and BNP , the latter of which has less natriuretic, diuretic, and vasodilatory activity than BNP . Several studies have suggested that elevated serum BNP levels may be a predictor for the progression or prognosis of DKD [70][71][72]. Thus far, however, no report has shown that increased BNP levels by DPP-4 inhibitors are associated with the pathogenesis of DKD.…”
Section: Bnpmentioning
confidence: 99%